Strategi Sekolah Menengah Kejuruan (SMK) Swasta Di Banten Dalam Membangun Brand Image Untuk Meningkatkan Kepercayaan Masyarakat - Hikmah, Mia Nurul; Handoko, Pryo (Professional: Jurnal Komunikasi dan Administrasi Publik, 2025)
This research analyzes strategies developed by private Vocational High Schools in Banten Province for building brand image to enhance public trust. The transformation of Indonesia's educational landscape presents complex competitive dynamics for private vocational education institutions in maintaining their existence and relevance. The study employs a qualitative approach using literature review methods through systematic analysis of relevant scientific literature from 2020-2025. Research findings indicate that effective brand image building strategies encompass four main dimensions: integrated digital marketing implementation, integration of educational excellence with stakeholder collaboration, optimization of visual media and institutional narratives, and integrated reputation management. Digital marketing strategies include optimization of digital traffic, conversion, and stakeholder engagement through diverse digital platforms. Integration of educational excellence with strategic collaboration involving industries, professional organizations, and government institutions proves to provide significant contribution in positioning private vocational schools as leaders in the competitive landscape. Factors influencing implementation effectiveness include internal dimensions such as human resource quality, management commitment, and facility availability, as well as external dimensions including competitive dynamics and public expectations. Primary challenges lie in limited digital marketing team competencies and complexities in building public trust. The research recommends developing continuous capacity building programs, integrated reputation management systems, and strategic collaboration with various stakeholders for optimizing sustainable brand image building strategies